2008
DOI: 10.1111/j.1365-2966.2008.13654.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the formation and evolution of isolated dwarf galaxies

Abstract: We present new fully self-consistent models of the formation and evolution of isolated dwarf galaxies. We have used the publicly available N-body/SPH code HYDRA, to which we have added a set of star formation criteria, and prescriptions for chemical enrichment (taking into account contributions from both SNIa and SNII), supernova feedback, and gas cooling. The models follow the evolution of an initially homogeneous gas cloud collapsing in a pre-existing dark-matter halo. These simplified initial conditions are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 80 publications
(112 reference statements)
11
121
0
Order By: Relevance
“…Large amounts of cold Herschel is an ESA space observatory with science instruments provided by European-led Principal Investigator consortia and with important participation from NASA. interstellar matter are unexpected in dEs, as both internal (supernova explosions) and external effects (ram-pressure stripping, galaxy interactions, tidal effects) are thought to be able to expel the gas from the shallow potential on short timescales (Michielsen et al 2004;van Zee et al 2004;Roediger & Hensler 2005;Boselli et al 2008a,b;Valcke et al 2008). That the Hi detected dEs are found preferentially near the edge of the cluster supports the idea that understanding environmental effects is crucial to constraining the evolutionary history of dEs.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Large amounts of cold Herschel is an ESA space observatory with science instruments provided by European-led Principal Investigator consortia and with important participation from NASA. interstellar matter are unexpected in dEs, as both internal (supernova explosions) and external effects (ram-pressure stripping, galaxy interactions, tidal effects) are thought to be able to expel the gas from the shallow potential on short timescales (Michielsen et al 2004;van Zee et al 2004;Roediger & Hensler 2005;Boselli et al 2008a,b;Valcke et al 2008). That the Hi detected dEs are found preferentially near the edge of the cluster supports the idea that understanding environmental effects is crucial to constraining the evolutionary history of dEs.…”
Section: Introductionsupporting
confidence: 53%
“…In particular, the population of dEs can be subdivided into nucleated and non-nucleated subclasses and several papers report evidence of disks, spiral structure, bars or star formation (e.g., Jerjen et al 2000;Barazza et al 2002;Geha et al 2003;Graham et al 2003a,b;De Rijcke et al 2003;Lisker et al 2006a,b). Kinematical studies demonstrate that dEs are not simple pressure-supported systems: some dEs seem to be rotationally supported (Simien et al 2002;Pedraz et al 2002;Geha et al 2003;De Rijcke et al 2003;van Zee et al 2004;Toloba et al 2009), whereas others show evidence of kinematically decoupled cores ; Thomas et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such intermittent star formation episodes occurring spontaneously in hydrodynamical simulations have been mentioned by Stinson et al (2007) and Valcke et al (2008). M#576 in Fig.2 offers the example of an intermediate mass self-regulated system (M i = 4.39 × 10 8 M ⊙ ).…”
Section: Self-regulationmentioning
confidence: 99%
“…Therefore, it is likely to be a critically important factor driving the evolution of low mass galaxies (e.g., Dekel & Silk, 1986;Mac Low & Ferrara, 1999;Ferrara & Tolstoy , 2000;Salvadori et al, 2008) like the Carina dSph, with M tot = 6.1 ± 2.3 × 10 6 M ⊙ within the half radius 241 ± 23kpc (Walker et al, 2009). If the bursts of star formation observed in Carina are part of an ongoing cycle of heating and cooling of an initial gas reservoir (e.g., Stinson et al, 2007;Valcke et al, 2008), there should be a clear evolutionary path in the observed abundances, showing the influence of SNe Ia enrichment at increasing [Fe/H] values. On the other hand, if the ISM is removed after each burst of star formation then new gas is required to power the subsequent star formation activity.…”
Section: Physical Interpretationmentioning
confidence: 99%